Psychological characteristics of adolescents with violent behavior - Monteiro, Inês Filipa de Azevedo (2022)
The objective of this systematic review is to synthesize the conclusions about the role of the peer group in the development of antisocial behavior. The bibliographic research was carried out in accordance with PRISMA guidelines, which aim to ensure clarity and transparency in systematic reviews, reducing the risk of bias and failure. The studies were identified through a search in different databases such as EBSCO, Pubmed and Web of Science. Of a total of 825 studies identified, 21 met the criteria. These 21 studies demonstrate a significant positive association between the influence of the peer group on the development of antisocial behavior. Four studies out of 21 demonstrate gender differences in relation to the relationship between peer groups and delinquency. Various forms of peer group influence such as peer behavior, peer reactions to adolescent behavior and peer pressure are identified in three studies. Characteristics of peers and/or the context of proximity to peers are also associated with involvement in delinquent behaviors, highlighted in six studies. Finally, two studies point out that characteristics of adolescents seem to be determinants for involvement in antisocial behaviors. In fact, there is evidence to support the relationship between a group of deviant peers and the development of antisocial behavior. However, it is necessary to consider another type of variables that can moderate and/or mediate this relationship, as well as the presence of other factors.